Test-retest reliability of the PDQ-Carer - Morley, D; Dummett, S; Kelly, L; Jenkinson, C (Elsevier, 2022)
Introduction: The PDQ-Carer is a 29-item measure of health-related quality of life (QoL) for use with carers of people with Parkinson’s (PwP). The measure produces a profile of scores across four domains. Previous validation data indicates that the measure possesses sound psychometric properties in terms of validity and internal consistency. An additional important attribute of any measure is test-retest reliability, i.e. the ability to provide stable results over time, presuming that there has been no change in the status of the construct being measured. To date, no assessment of the test-retest reliability of the PDQ-Carer has been undertaken.